Understanding tissue-resident macrophages unlocks the potential for novel combinatorial strategies in breast cancer - Biswas, Manjusha (Frontiers in Immunology, 2024)
Tissue-resident macrophages (TRMs) are an integral part of the innate immune system, but their biology is not well understood. Distinctive resident macrophage populations are identified in different organs in mice and in human tissues using fate mapping studies. They develop from the yolk sac and self-maintain themselves lifelong in specific tissular niches. Similarly, breast resident macrophages are part of the mammary gland microenvironment. They reside in the breast adipose tissue stroma close to the ductal epithelium and help in morphogenesis. In breast cancer, reprogrammed TRMs may promote disease progression and metastasis, however precise mechanisms have not been elucidated. TRMs interact intimately with recruited macrophages, cytotoxic T cells and other immune cells along with cancer cells, deciding further immunosuppressive or cytotoxic pathways. Moreover, triple-negative breast cancer (TNBC), which is generally associated with poor outcomes, can harbor specific TRM phenotypes. The influence of TRMs on adipose tissue stroma of the mammary gland also contributes to tumor progression. The complex crosstalk between TRMs with T cells, stroma and breast cancer cells can establish a cascade of downstream events, understanding which can offer new insight for drug discovery and upcoming treatment choices. This review aims to acknowledge the previous research done in this regard while exploring existing research gaps and the future therapeutic potential of TRMs as a combination or single agent in breast cancer.